ANALISIS PEMAHAMAN PERAWAT TERHADAP PELAKSANAAN RONDE KEPERAWATAN DI RUANG PERAWATAN RSUD OTANAHA KOTA GORONTALO - Agustiar Darmawan Bagu; Sabirin B. Syukur (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Nursing rounds are a professional nursing care management carried out by nurses to overcome nursing problems experienced by clients. The aim is to analyze the nurse's understanding of the implementation of the round. This study uses a situation analysis study method, namely the fishbone diagram approach to get to the root of the problem related to nursing rounds and nurses' consideration at the hospital. With as many as 8 nurses. This study uses data collection procedures by observing and documenting. Based on the results of the study, it was found that those who said it was always 2 respondents or 25.0%, those who said it was often 4 respondents or 50.0%, and those who said it rarely were 2 respondents or 25.0%.